Pengaruh Model Pembelajaran Course Review Horay terhadap Kemampuan Pemahaman Materi Teks Tanggapan Siswa di UPTD SMP Negeri 4 Gunungsitoli Idanoi - Friska Sotania Bate’e; Noibe Halawa; Imansudi Zega; Lestari Waruwu (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study aims to determine the effect of the Course Review Horay learning model on students' comprehension ability in response text material at SMP Negeri 4 Gunungsitoli Idanoi. This learning model is an active and fun strategy that combines game elements with learning activities, so it is expected to increase student engagement and understanding of the material. The study used a quasi-experimental approach with a Non-Equivalent Control Group Design. The research procedure included three stages, namely (1) implementing a pre-test to measure students' initial abilities, (2) providing treatment by applying the Course Review Horay model in the experimental class and conventional learning in the control class, and (3) implementing a post-test to determine the increase in students' comprehension abilities. The study population was all seventh grade students consisting of two classes, namely VII-A and VII-B, each consisting of 20 students, so that the total number of participants was 40 people. Sampling used a saturated sampling technique because the entire population was sampled. The independent variable in the study was the application of the Course Review Horay learning model, while the dependent variable was student learning outcomes in the response text material. The results of data analysis showed a significant difference between student learning outcomes in the experimental class and the control class. Based on the hypothesis test, the t-value was 12.006, with a significance (2-tailed) <0.001, which is smaller than 0.05.